Effect of mechanical properties of the lower limb muscles on muscular effort during table tennis forehand - Iino, Y.; Yoshioka, S.; Fukashiro, S. (ISBS Proceedings Archive (Michigan), 2018)
This study investigated the effect of the maximum isometric forces and the maximum shortening velocities of the lower limb muscles on the muscular effort during the table tennis forehand. Four male collegiate players performed table tennis forehand drives with maximum effort. We used OpenSim`s static optimization algorithm to estimate the activation patterns of lower limb muscles. The cost function was the sum of squared muscle activations for all lower limb muscles, which we will refer to as the muscular effort. The simulations were repeated with the maximum isometric forces or the maximum shortening velocities of each muscle group changed by ±10% of their original values. The results suggest that increasing the maximum isometric forces of the hip extensors and adductors may be most effective to reduce the muscular effort.